Arquitetura h??brida terrestre/sat??lite para distribui????o de conte??dos em ??reas remotas com 5G - Rezende, Tib??rio Tavares (2020)
Considering the advancement of exponential technologies and the effects on the current scenarios of generation, control and transmission of information, the 5G enviroment wil require satellite technology for the deployment of weirelles acess networks in remote or underserverd areas, playing en important role alongside existing terrestrial technologies.